Coherent Manipulation of Single Electrons with Optical Photons in Condensed Helium‐4. Issue 6 (6th May 2020) - Otten, Matthew; Zhou, Xianjing; Zhang, Xufeng; Jin, Dafei
Abstract: Single electrons are one of the simplest quantum objects in nature. In free space or conventional materials, single electrons hardly interact with optical (ultraviolet‐visible‐infrared) photons, so their quantum states cannot be easily manipulated by optics. Here, a notable exception is theoretically demonstrated: a single electron in condensed helium‐4 can be self‐confined in a nanometric bubble of 1 to 2 nm radius and resonantly interact with mid‐infrared photons of 3 to 12 µm wavelength. A femtosecond laser can drive the electron into Rabi oscillations and prepare it onto arbitrary superposition states between the ground and excited states. After the laser pulse, the electron bubble can exhibit remarkable nonequilibrium quantum dynamics and evolve toward various final states with various lifetimes. These processes are accompanied with intense phonon radiation. Abstract : A nanometric single electron trapped in superfluid helium‐4 can resonantly interact with mid‐infrared photons. It is theoretically demonstrated that a femtosecond laser pulse can drive such a single electron into Rabi oscillations and prepare its quantum state onto an arbitrary superposition between the ground and excited states. After the laser pulse, the electron can exhibit remarkable nonequilibrium quantum dynamics.